Two Years of Improved Neurological Function With Nusinersen in a 48-Year-Old Patient With Spinal Muscular Atrophy Type 3. Issue 5 (September 2020) - Shah, Jaimin S.; Rubin, Devon I.; Dimberg, Elliot L.; Owens, Christina R.; Gicalone, Angelica R.; De Oliveira, Gleydiane; Oskarsson, Björn E.
Abstract : Introduction: Nusinersen antisense oligonucleotide infusions have been shown to be effective in the treatment spinal muscular atrophy. The majority of the evidence has been collected in young type 1 and type 2 patients, and evidence of efficacy in adult patients is limited. Case Report: A 48-year-old woman with spinal muscular atrophy type 3 who has received the loading dose and 8 maintenance infusions over an 8-month period. Grip and pinch strength, measured by hand-held dynamometry measured at baseline and in 6 to 12 months interval improved over a 24-month period. She also reported multiple other subjective improvements in function. Conclusions: This is the first published case of nusinersen in a middle-aged adult with spinal muscular atrophy. Sustained clinically meaningful improvement may be possible with nusinersen initiation in mid adulthood.